1991
DOI: 10.1021/j100162a023
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and assignments for 1-fluoro- and 1-chlorocyclobutenes: revised assignment for cyclobutene

Abstract: 3549Mass spectroscopic Knudsen cell studies of the vapor over P4OI0(H) at 150, 315, and 400 OC have shown that P4OIo undergoes a phase transition which lowers the vapor pressure at 300 OC and that the vapor is composed of P4O10, P409, and P408 molecules with an approximate ratio of 10:3:1; furthermore, the decomposition products P408 and P407 showed increased concentration with higher Knudsen cell temperat~res.'~ While species such as P30e7' were produced by 40-eV electron impact, they showed no temperature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…We have analyzed the character of the normal modes and must agree with Negri and co-workers 152 that the assignment 150,151 on which Mathies 147 based his interpretation is incorrect. Although there is some component of disrotatory motion in the 1075 cm -1 normal mode, the mode is dominantly a CH 2 wag.…”
Section: Photochemicalsupporting
confidence: 52%
See 1 more Smart Citation
“…We have analyzed the character of the normal modes and must agree with Negri and co-workers 152 that the assignment 150,151 on which Mathies 147 based his interpretation is incorrect. Although there is some component of disrotatory motion in the 1075 cm -1 normal mode, the mode is dominantly a CH 2 wag.…”
Section: Photochemicalsupporting
confidence: 52%
“…147 Intensity was observed in an overtone of the 1075 cm -1 (ν 15 ) normal mode at 2150 cm -1 , implying that the corresponding motion plays a significant role in the excited state dynamics on a time scale shorter than that of the resonance Raman experiment (≈50 fs). Earlier work 150,151 indicated that the ν 15 normal mode (b 1 symmetry) is of disrotatory character. (Note that the disrotatory and conrotatory modes are not normal modes.)…”
Section: Photochemicalmentioning
confidence: 99%
“…This trend is consistent with the Diels−Alder reactivities of different alkenes discussed in this contribution. The increase in distortion energy of dihedral angles indicates an increase of out-of-plane bending force constants from cyclopropene to cyclohexene, which is confirmed by the C−H out-of-plane vibration frequency observed in IR spectra of cycloalkenes (γ-CH out-of-plane bend of cycloalkenes 5−8 are 570, 33 635, 34 695, 35 and 718 cm −1 , 36 respectively). This trend in bending force constants is in accord with the change of hybridization states of the olefinic carbons suggested by the natural bond orbital (NBO) analysis.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 62%
“…For the case of cyclohexadiene, this prediction (conrotatory) has been experimentally confirmed using both stereochemical analysis of the products in alkyl-substituted reactants and resonance Raman spectroscopy. , Somewhat surprisingly, the results for the smaller cyclobutene (CB) molecule are less conclusive. Alkyl substitutions of CB have produced mixtures of allowed (disrotatory) and forbidden (conrotatory) photoproducts and, because of controversies in the assignment of some bands, , the interpretation of resonance Raman experiments , (which provide a more direct probe of the excited-state dynamics) has been questioned . On the basis of the original assignment of the vibrational force field of CB, and a later assignment by Craig and co-workers, the resonance Raman spectrum 13 has been interpreted to show traces of a disrotatory ring opening. , However, on the basis of their own assignment of the vibrational force field and on their interpretation of the assignment of Wiberg and Rosenberg, Negri and co-workers 15 concluded that the resonance Raman spectrum does not show “any positive hint of the activity of distrotatory ring opening motion.”…”
mentioning
confidence: 99%